ANALISIS PENGELOLAAN KEUANGAN IBU RUMAH TANGGA PASCA PANDEMI COVID-19 DALAM MENCIPTAKAN KESEJAHTERAAN KELUARGA: Studi Kasus pada IRT di Dusun Babakan Desa Panumbangan Kabupaten Ciamis - Nisa Zakiah; Ai Nur Solihat; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in this research is related to the financial management of housewives after the Covid-19 pandemic, which experienced ups and downs, as well as their efforts to create a prosperous family. This research was conducted with the aim of knowing the financial management of housewives after the Covid-19 pandemic in creating family prosperity in Babakan Hamlet, Panumbangan Village, Ciamis Regency. The method used in this research is a case study method in a qualitative approach with data collection techniques through observation, interviews and documentation. The analysis technique goes through three stages, namely data reduction, data presentation and verification. The research subjects who were used as informants were 7 people consisting of 3 housewives as key informants and the remaining 4 people including 3 husbands and the village head as supporting informants. From the research results, it was found that housewives' financial management after the Covid-19 pandemic had different results, including good, quite good, to poor financial management. To achieve family welfare for 3 housewives in Babakan Hamlet, there are different categories where the results show that they fall into Prosperous Family Stage I, Prosperous Family Stage III, and Prosperous Family Stage III Plus.